2011
DOI: 10.2217/pme.11.87
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Education of Pharmacists Regarding Pharmacogenetic Testing

Abstract: Most pharmacists were interested in learning more about pharmacogenetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 18 publications
6
82
2
Order By: Relevance
“…In U.S., seven studies have revealed consistent positive attitudes towards PG among pharmacists; 67% felt that PG should be focal point in patient care, 17 83% of pharmacists believed that genetic can improve patients outcomes, 15 more than half of participants felt that PG can reduce ADRs and has promising benefits to healthcare systems. [16][17][18][19]26 Similar findings were revealed from UK that 80-95% considered PG as beneficial to patients, despite reported gross limited knowledge of PG reflected in only 6% felt well informed about PG; 9 from Malaysia 67% of pharmacists felt that PG is very important in drug safety; 12 these is in agreement with findings from Australia 24 and Nigeria. 20 Recently from Ukraine, 87% of future pharmacists perceived benefits from PG, but only one-third (1/3) of the participants that correctly understood PG and 70% not aware of PG 25 and this is comparable with results from Canada.…”
Section: Attitudes-perceived Benefitssupporting
confidence: 75%
See 2 more Smart Citations
“…In U.S., seven studies have revealed consistent positive attitudes towards PG among pharmacists; 67% felt that PG should be focal point in patient care, 17 83% of pharmacists believed that genetic can improve patients outcomes, 15 more than half of participants felt that PG can reduce ADRs and has promising benefits to healthcare systems. [16][17][18][19]26 Similar findings were revealed from UK that 80-95% considered PG as beneficial to patients, despite reported gross limited knowledge of PG reflected in only 6% felt well informed about PG; 9 from Malaysia 67% of pharmacists felt that PG is very important in drug safety; 12 these is in agreement with findings from Australia 24 and Nigeria. 20 Recently from Ukraine, 87% of future pharmacists perceived benefits from PG, but only one-third (1/3) of the participants that correctly understood PG and 70% not aware of PG 25 and this is comparable with results from Canada.…”
Section: Attitudes-perceived Benefitssupporting
confidence: 75%
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the community setting, the internal CPD also may predict the pharmacists' knowledge and the outpatient's service hour could predict pharmacist' attitude. Previous study stated that some characteristics like sex, age, level of education type of service and the intensity of CPD [16][17][18]. Roeder et al showed that pharmacists with Pharm D degree had better knowledge than the lower degree [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study stated that some characteristics like sex, age, level of education type of service and the intensity of CPD [16][17][18]. Roeder et al showed that pharmacists with Pharm D degree had better knowledge than the lower degree [17]. Pharmacist who worked in the community or hospital less than 5 years had good interests in pharmacogenetic than pharmacists who work more than 5 years [16].…”
Section: Discussionmentioning
confidence: 99%